Dual Role of MtHAC-1 in Regulating Cellulase and Xylanase Production in Myceliophthora thermophila. - Lai, Yapeng; Wang, Juan; Xie, Ning; Liu, Gang; Lacap-Bugler, Donnabella C (Wiley, 2025)
Filamentous fungi produce large quantities of cellulase and xylanase as extracellular enzymes to degrade plant-derived polysaccharides. This process is controlled by a complex network of transcription factors (TFs). Here, we present the bZIP TF Mthac-1 exhibiting dual regulatory effects on the production of cellulase and xylanase in Myceliophthora thermophila. The deletion of Mthac-1 reduced the cellulase and xylanase activities and protein secretion during the early phase of cultivation but enhanced in the middle and late stages of cultivation, compared with the wild-type (WT) strain. It also led to fungal growth defects, characterised by few hyphal branching and reduced conidiation. Real-time quantitative reverse transcription PCR (RT-qPCR) analysis showed that Mthac-1 dynamically regulates the expression of major cellulase genes. Furthermore, electrophoretic mobility shift assays (EMSAs) demonstrated that Mthac-1 directly binds to the promoter regions of the β-glucosidase gene bgl1 (MYCTH_66804), cellobiohydrolase gene cbh1 (MYCTH_109566), endoglucanase gene egl2 (MYCTH_86753), xylanase gene xyn1 (MYCTH_112050) and the regulatory gene xyr1 (MYCTH_2310145), exhibiting higher binding affinity for xyn1 and xyr1. The comparative transcriptomic analysis indicated that Mthac-1 also plays an important role in the expression of 26S proteasome-encoding genes under cellulolytic conditions. This work provides new insights into the regulatory mechanisms underlying cellulase and xylanase gene expression with potential applications in fungal strain engineering in biorefinery industries.
Keywords: Myceliophthora thermophila; Mthac‐1; cellulase; comparative transcriptomics; gene expression; xylanase; 0605 Microbiology; 3106 Industrial biotechnology; 3107 Microbiology; Cellulase; Gene Expression Regulation, Fungal; Sordariales; Endo-1,4-beta Xylanases; Promoter Regions, Genetic; Basic-Leucine Zipper Transcription Factors; Fungal Proteins